Proteomic Profiling of Dilated Cardiomyopathy Plasma Samples ─ Searching for Biomarkers with Potential to Predict the Outcome of Therapy - Klimentova, Jana; Rehulka, Pavel; Stulik, Jiri; Vozandychova, Vera; Rehulkova, Helena; Jurcova, Ivana; Lazarova, Marie; Aiglova, Renata; Dokoupil, Jiri; Hrecko, Juraj; Pudil, Radek (Journal of proteome research, 2024)
Determination of the prognosis and treatment outcomes of dilated cardiomyopathy is a serious problem due to the lack of valid specific protein markers. Using in-depth proteome discovery analysis, we compared 49 plasma samples from patients suffering from dilated cardiomyopathy with plasma samples from their healthy counterparts. In total, we identified 97 proteins exhibiting statistically significant dysregulation in diseased plasma samples. The functional enrichment analysis of differentially expressed proteins uncovered dysregulation in biological processes like inflammatory response, wound healing, complement cascade, blood coagulation, and lipid metabolism in dilated cardiomyopathy patients. The same proteome approach was employed in order to find protein markers whose expression differs between the patients well-responding to therapy and nonresponders. In this case, 45 plasma proteins revealed statistically significant different expression between these two groups. Of them, fructose-1,6-bisphosphate aldolase seems to be a promising biomarker candidate because it accumulates in plasma samples obtained from patients with insufficient treatment response and with worse or fatal outcome. Data are available via ProteomeXchange with the identifier PXD046288.
Keywords: Proteomics; hemokoagulace; proteom; dilated cardiomyopathy; Proteome; Cardiomyopathy, Dilated; left ventricular reverse remodeling; Humans; biologické markery; LFQ; lidé; Biomarkers; Blood Coagulation; functional enrichment analysis; proteomics; plasma proteome profiling; dilatační kardiomyopatie; proteomika